Design and performance evaluation of hybrid dryer with desiccant dehumidifier and regeneration system - Dela Cruz, Efren A.; Berana, Menandro S. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Drying is one of the major aspects of agricultural production, processing and manufacturing, most products need drying before these can be processed further and marketed. Because of the weather conditions in the Philippines and the unpredictable effect of climate change, it is necessary to resort to artificial drying. The use of large amounts of fossil fuels for conventional hot air dryers are also subject to significant shortcomings. High temperature drying may damage the physical appearance of product, and can cause breakdown of enzymes. Fumes from burning diesel and other fuels can also impart adverse odor or taste to the product being dried, which makes the product unsuitable for consumption. In tropical countries like the Philippines, fuel-fired dryers are used to provide the required temperature difference for drying. As a result, drying by heated air becomes costly, and inefficient. It also damaged the physical appearance and quality of products being dried. To address these issues, the possibility of reducing the actual moisture content of drying air was studied using desiccant dehumidification with hybrid solar, biomass and heat pump drying system. This study aims to develop and investigate a Hybrid Dryer (solar-biomass and heat pump with desiccant dehumidifier and regeneration system) which brings together hot air and desiccant drying system in reducing the moisture content of drying air which could be used even at low temperature drying for heat sensitive products, and with the combination of solar, biomass and heat pump system for heating and regeneration of desiccant. Pre-testing shows that solar collector may increase the air outside temperature from 32.6°C to more than 46°C and decrease its relative humidity from 62.2% outdoor condition to 31.3%. The heat pump components further increase the temperature of regeneration air by 7°C with an average of 4.74 °c, and further decrease the relative humidity by 12%, with an average of 6.48%. Dehumidifying the drying air increases its temperature and provides greater decrease in the relative humidity as compared to relative humidity of air in drying chamber as provided only by the solar collector from outside condition of 51.4% to final RH of 11.J %. The gasifier further increased the temperature of air to more than 53°C for regeneration as required for absorbing the moisture from the desiccant. The developed drying system could dry the samples from initial weight of 500g with 88.37% moisture content to a final weight of 60.97g with 0.56% moisture content before the drying process ceases. The required moisture content of 5% can be attained for less than 29 hours of drying with power consumption of 15k W -h. Comparing the initial cost of the developed drying system, it was about 50 to 60% less compared to that of the electric drying system with nearly the same capacity. Although, electric dryer dries the product quicker by more than 10 hours or only 60% of the time required using the hybrid drying system in attaining the required moisture content, the developed system consumes only 19.67% to 26.36% as compared to the consumption of electric dryer with an average of 25.65% in every hour of operation and consumes about 42% of electric dryer's needed energy to attain the required moisture content of the dried product. The specific moisture extraction rate (SMER) of hybrid dryer had an average of about three times greater as compared to that of the electric dryer, because of the great difference in the energy consumption during drying. This also means that the cost of drying using the hybrid dryer is more economical as compared to that of the electric dryer since it can dry three times more moisture than the electric dryer in every k W -hr of energy consumed. The tabulated mean on the sensory evaluation on the product dried using hybrid and electric dryer conducted in CLSU-Agriculture and Food Technology Business Incubator Science City of Munoz, Nueva Ecija for aroma, color, flavor and texture shows significant differences with the degree of freedom of 14 at 5% level of significance. It is concluded that the aroma of dried onion using the developed dryer is much pronounced than that of using the electric dryer in which the onion has a slightly pronounced aroma. Onion dried using the developed dryer has dark brown color while onion using the electric dryer has red onion to brown in color. Onion dried using the electric dryer has pronounced onion flavor compared to that of the developed dryer which has only slightly pronounced onion flavour. Furthermore, the onion processed using the hybrid dryer was moderately saggy while the one using the electric dryer was firm. Based on the results, the drying objectives were attained, even though the sensory evaluation failed. This was caused by post-process rehydration and storage because the dried product using the hybrid dryer was stored six months longer than the storage period of that using the electric dryer prior to the sensory evaluation.
Thesis (Ph.D. Energy Engineering)--University of the Philippines Diliman
Keywords: Drying; Drying apparatus -- Design and construction